2010
DOI: 10.5004/dwt.2010.2991
|View full text |Cite
|
Sign up to set email alerts
|

Removal of lead, cadmium, and mercury ions using biosorption

Abstract: The biosorption of Pb (II), Cd (II), and Hg (II) from simulated aqueous solutions using baker's yeast biomass was investigated. Batch type experiments were carried out to find the equilibrium isotherm data for each component (single, binary, and ternary), and the adsorption rate constants. Kinetics pseudo-first and second-order rate models applied to the adsorption data to estimate the rate constant for each solute, the results showed that the Cd (II), Pb (II), and Hg (II) uptake process followed the pseudo-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Biosorption is an innovative technology that employs inactive and dead biomass for the removal and recovery of metals from aqueous solutions (Romera et al, 2007;Cui and Grace, 2007). Various biomasses such as bacteria (Ridha, 2011), sludge (Ali, 2011), yeast (Sulaymon et al, 2010), algae (Kratochvil, 1997), fungi (Brady et al, 1999) and plants (Melcakova and Ruzovic, 2010) have been used to adsorb metal ions from the environment. Among the most promising types of biosorbents studied are algal biomass (Romera et al, 2006;Figueria et al, 2000), algal biomass have been reported to have high metal binding capacities due to their containing of functional groups on the cell wall.…”
Section: Introductionmentioning
confidence: 99%
“…Biosorption is an innovative technology that employs inactive and dead biomass for the removal and recovery of metals from aqueous solutions (Romera et al, 2007;Cui and Grace, 2007). Various biomasses such as bacteria (Ridha, 2011), sludge (Ali, 2011), yeast (Sulaymon et al, 2010), algae (Kratochvil, 1997), fungi (Brady et al, 1999) and plants (Melcakova and Ruzovic, 2010) have been used to adsorb metal ions from the environment. Among the most promising types of biosorbents studied are algal biomass (Romera et al, 2006;Figueria et al, 2000), algal biomass have been reported to have high metal binding capacities due to their containing of functional groups on the cell wall.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, attention to new natural low-cost materials as biosorbents with high metal-binding capacity , as alternatives to activated carbon, have been considered in a number of investigations (Rae & Gibb, 2003;Ulmanu et al, 2003;Bishnoi & Garirna, 2005;Cochrane et al, 2006;Sulaymon et al, 2010). These biomass include: chitin and chitosan, macroalgae, activated waste sludge, yeast, and fungi.…”
Section: Introductionmentioning
confidence: 99%